Structural architecture and late Cenozoic tectonic evolution of the Ulsan Fault Zone, SE Korea: New insights from integration of geological and geophysical data - Cheon, Youngbeom; Shin, Young Hong; Park, Samgyu; Choi, Jin-Hyuck; Kim, Dong-Eun; Ko, Kyoungtae; Ryoo, Chung-Ryul; Kim, Young-Seog; Son, Moon (Frontiers in Earth Science, 2023)
Integration of geological and geophysical data is essential to elucidate the configuration and geometry of surface and subsurface structures, as well as their long-term evolution. The NNW–SSE-striking incised valley and parallel mountain range in the southeastern margin of the Korean Peninsula, extending 50 km from Gyeongju to Ulsan cities, are together regarded as one of the most prominent geographical features in South Korea. This paper presents an investigation into the structural architecture and deformation history of the valley and range during late Cenozoic based on combined data from field observations and gravity and electrical resistivity surveys. Our results based on integrated and reconciled geological and geophysical data are as follows. First, the incised fault valley can be divided into (1) the northern part, which comprises several distributed buried or exposed fault strands; and (2) the southern part, which comprises a concentrated deformation zone along the eastern margin of the valley. Different deformation features between the two parts are controlled by the lithology of host rocks and by the location and geometry of the neighboring major structures, that is, the Yeonil Tectonic Line (YTL) and the Yangsan Fault. Second, we defined the Ulsan Fault Zone as a NNW–SSE- to N–S-striking fault within the incised valley and along the eastern margin of the valley. In particular, the constituent strands located along the eastern margin of the valley have acted mainly as an imbricate thrust zone, characterized by an east-side-up geometry with moderate to low dip angles and reverse-dominant kinematics in the shallow subsurface during Quaternary. Third, reactivated strands within the Ulsan Fault Zone during Quaternary are interpreted as shortcut faults developed in the footwall of Miocene subvertical structures, predominantly the YTL. In addition, movements on the Ulsan Fault Zone and the YTL during Miocene to Quaternary were arrested by the NNE–SSW-striking Yangsan Fault, which was a prominent and mature structure. Our results highlight the spatiotemporal structural variation in SE Korea and emphasize the strong control of the configuration and geometry of pre-existing structures on the distribution and characteristics of the subsequent deformation under changing tectonic environments through late Cenozoic.